Strengthening Public Health through Screening and Early Education on The Month of Immunization Program in Elementary Schools in Gunung Anyar, Surabaya: Penguatan Kesehatan Masyarakat melalui Program Skrining dan Edukasi saat Imunisasi BIAS di Sekolah Dasar - Leonardo Tedjaprasadja (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Screening activities and immunization programs at elementary schools in the Gunung Anyar District, Surabaya are important pillars in efforts to prevent disease and maintain public health, especially in children. Screening activities are needed to detect certain health conditions, both physical and mental, that require further treatment. This is important to ensure that every child can grow and develop optimally, and to identify health problems as early as possible so that appropriate interventions can be carried out. The BIAS (Monthly School Children's Immunization) program aims to provide immunization to school-age children to gain immunity to diseases that can be prevented by vaccination. Screening activities and health education during BIAS immunization are very important to be carried out periodically by involving health workers, schools, and parents. This can improve the health of the community so that public health goals can be achieved optimally. The implementation of educational activities has gone well. The sustainability of activities is realized in the formation of foster families, which are monitored until the targeted increase in health levels is achieved.